Nurses' experiences of discrimination in health care: A qualitative study in Iran - Mohammadjavad Hosseinabadi-Farahani; Narges Arsalani; Mohammadali Hosseini; Eesa Mohammadi; Masoud Fallahi-Khoshknab (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Justice in health is one of the main concerns of health organizations, and discrimination in health care is one of the negative outcomes to achieving this goal. Hence, a full understanding of the phenomenon of discrimination in health care and adopting strategies to eliminate it is necessary. The present study was conducted to explore and describe the experiences of nurses of discrimination in health care. MATERIALS AND METHODS: The present qualitative content analysis study was conducted between 2019 and 2020. Data were collected through semi-structured interviews with 18 participants (two physicians, three nursing supervisors, two head nurses, four clinical nurses, two nursing assistants, and three hospitalized patients) in one public and one private hospital in the city of Tehran. The participants were selected by purposive sampling, which continued until saturation of data. Data obtained were analyzed using the Graneheim and Lundman method. RESULTS: Four main categories and 14 subcategories were extracted from data analysis: 1) habitual discrimination (everyday discrimination in health centers, ignoring patient rights, low levels of trust in medical staff); 2) interpersonal relationships (expectations of associates, respect for colleagues and friends, the possibility of the occurrence of similar situations, reciprocating people's favors); 3) shortage of health-care resources (shortage of medical equipment, heavy workload, infrastructure of medical centers, lack of access to physicians); and 4) favoritism (ethnicity, favoritism as a common method, and favoritism as the ultimate solution to treatment problems). CONCLUSION: The present study revealed certain dimensions of discrimination in health care that remain hidden in many quantitative studies. It appears that health system managers will be able to move toward eliminating discrimination in health care. Thus, designing effective models to reduce discrimination in health care based on the underlying concepts of this study is recommended.